PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH E-WOM TERHADAP PURCHASE INTENTION PADA AMOLAS CAFÉ CANGGU - Putri, Putu Adnyani; Aksari, Ni Made Asti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
Purchase intention is consumer’s intent to buy a product based on their previous experiences and usage. This study aims to examine the role of brand image in mediating the effect of electronic word of mouth (E-WOM) on purchase intention. This research was conducted at Amolas Café Canggu. The samples used for this study is 120 respondents determined using nonprobability sampling, in particular purposive sampling method. Data was collected using online questionnaire and analysed using path analysis. The results of this study show that electronic word of mouth (E-WOM) has a positive and significant effect on purchase intention and brand image; brand image has a positive and significant effect on purchase intention; and brand image partially mediate the effect of electronic word of mouth (E-WOM) on purchase intention. This implies that to create consumer’s purchase intention, Amolas Café Canggu should pay attention to its brand image and electronic word of mouth.